2020
DOI: 10.3390/jcm9092811
|View full text |Cite
|
Sign up to set email alerts
|

NGAL Correlates with Femoral and Carotid Plaque Volume Assessed by Sonographic 3D Plaque Volumetry

Abstract: Background/Objectives: Inflammation represents a cornerstone in the development of atherosclerosis and early detection is essential to avoid cardiovascular events. Biomarkers like interleukin-1 beta, interleukin-6, or high sensitivity CRP (hs-CRP) have been investigated intensively in this field. Since they have several limitations, additional biomarkers are needed for cardiovascular risk stratification. The acute phase protein, neutrophil gelatinase-associated lipocalin (NGAL), modulates inflammation and is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
(13 reference statements)
1
6
0
Order By: Relevance
“…In our study, hs-CRP showed no significant correlation with baseline plaque volume. This has also been shown in a previous publication [ 22 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, hs-CRP showed no significant correlation with baseline plaque volume. This has also been shown in a previous publication [ 22 ].…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the presence of chronic kidney disease and male sex is associated with higher plaque volume [ 21 ]. The biomarker neutrophil gelatinase-associated lipocalin, but not hsCRP was shown to correlate with peripheral plaque volume at baseline [ 22 ]. The purpose of our study was to evaluate the effect of cardiovascular biomarkers, in particular fetuin-A and hsCRP, on atherosclerotic plaque progression.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it seems that NGAL could be an encouraging inflammatory biomarker to predict cases with asymptomatic atherosclerosis. 131 …”
Section: Inflammatory Biomarkers In Atherosclerosismentioning
confidence: 99%
“…The chi-square test was used to compare categorical variables. Total PV was divided into high (501-2048 mm 3 ) and low (0-500 mm 3 ) total PV, with the 75th percentile as the cut-off point for some calculations, as described previously [34].…”
Section: Discussionmentioning
confidence: 99%